COMPRESSIVE STRENGTH ANALYSIS OF CONCRETE USING ASPHALT SCRAP WASTE - MUHAMMAD RIFA'I; YONAS PRIMA ARGA RUMBYARSO; INDRIASARI (INTERNATIONAL JOURNAL OF MULTI SCIENCE, 2025)
Concrete is one of the most commonly used building materials in civil construction and is widely used by various groups. Currently, the rapid growth of the global economy has led to various upgrades of concrete building construction systems in various places, resulting in an increase in concrete production. With the development of technology in concrete, more and more ideas and innovations are used to improve the quality of concrete, one of the innovations is by adding additional or substitute materials to concrete. One of the substitute materials that can be used is asphalt scrap waste. This study aims to determine the compressive strength of concrete by utilizing asphalt scrap waste as a partial substitute for coarse aggregate. This research was conducted by comparing the effect of using scrap asphalt waste on the compressive strength of normal concrete. This research method is by conducting experiments or experiments in the concrete laboratory. This research refers to SNI-03-2834-2000, about Procedure for Making Normal Concrete Plan. Based on the research results, it can be concluded that the average normal concrete compressive strength value is 25.57 MPa, so it meets the planned concrete compressive strength of 25 MPa. The average concrete compressive strength of 5% scrap asphalt waste variation is 24.88 MPa, the average concrete compressive strength of 10% scrap asphalt waste variation is 23.86 MPa. Based on these results, that the greater the use of scrap asphalt waste, the compressive strength of concrete decreases.